Economic costs of diabetes in Saudi Arabia - Abdulkarim K Alhowaish (Wolters Kluwer Medknow Publications, 2013)
Background: Diabetes imposes a large economic burden on the individual, national healthcare systems, and countries. Objective: To determine the economic impact of diabetes mellitus on Saudi healthcare system, both now and in the future. Materials and Methods: This research study uses a prevalence-based approach that combines the demographics of the population (classified by nationality, sex and age group) with and without diagnosed diabetes in 1992 and 2010. The economic impact of diabetes is estimated in this study, using secondary sources of information provided by Ministry of Health, Ministry of Finance and Central Department of Statistics and Information databases. Results: People diagnosed with diabetes, on average, have medical healthcare expenditures that are ten times higher ($3,686 vs. $380) than what expenditures would be in the absence of diabetes. Over 96% of all medical healthcare expenditures attributed to diabetes are incurred by persons of Saudi nationality, with the remaining 4% incurred by persons of non-Saudi nationality. The population age 45-60 incurs 45% of diabetes-attributed costs, with the remaining population under age 15 incurs 3.8%, age 15-44 incurs 27.5%, and age 60 and above incurs 23.8%. Conclusion: The actual national healthcare burden because of diabetes is likely to exceed the $0.87 billion estimated in this study, because it omits the indirect costs associated with diabetes, such as absenteeism, lost productivity from disease-related absenteeism, unemployment from disease-related disability, lost productivity due to early mortality by disease. The social cost of intangibles such as pain and suffering and care provided by non-paid caregivers as well as healthcare system administrative costs, cost of medications, clinician training programs, and research and infrastructure development is also omitted from this research study. Further studies are needed to confirm the present findings and to improve our understanding of economic costs of diabetes and its related complications.